Peran Tata Kelola dan Implementasi Enterprise Risk Management Terhadap Market Value - Liyundira, Fetri Setyo; Ana, Selvia Roos; Heni, Heni (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Financial information as a medium commonly used by stakeholders is not the only determinant in assessing a company. The non-financial information conveyed also has significant value in investment considerations. The research aims to empirically prove testing and analysis regarding the impact of Enterprise Risk Management (ERM) on Market Value, with Good Corporate Governance (GCG) as a moderator. The research used a population of 112 manufacturing companies for the period 2019-2021 which were listed on the Indonesian Stock Exchange. The main variables used in the research are enterprise risk management, good corporate governance, and market value. The method for determining the hypothesis is through multiple linear regression. The results prove that ERM has a positive and significant influence on market value. GCG also shows results that strengthen the relationship between enterprise risk management and market value in 2019-2021 in companies listed on the Indonesian Stock Exchange, especially manufacturing companies.